Elucidating target specificity of the taccalonolide covalent microtubule stabilizers employing a combinatorial chemical approach - Lin Du (Nature Portfolio, 2020)
Taccalonolide microtubule stabilizers covalently bind β-tubulin and overcome taxane resistance mechanisms. Here, the authors synthesized fluorogenic taccalonolide probes and investigated the specificity of taccalonolide binding to β-tubulin and the molecular interactions between drug and target,